Dance of Thieves (Dance of Thieves #1) - Mary E. Pearson (USA Square Fish, 2018)
When the patriarch of the Ballenger empire dies, his son, Jase, becomes its new leader. Even nearby kingdoms bow to the strength of this outlaw family, who have always governed by their own rules. But a new era looms on the horizon, set in motion by a young queen, which makes her the target of the dynasty's resentment and anger. At the same time, Kazi, a legendary former street thief, is sent by the queen to investigate transgressions against the new settlements. When Kazi arrives in the forbidding land of the Ballengers, she learns that there is more to Jase than she thought. As unexpected events spiral out of their control, bringing them intimately together, they continue to play a cat and mouse game of false moves and motives in order to fulfill their own secret missions.
Keywords: Fiction; Dystopia; Fantasy; Adventure; Young Adult; Romance